Liability, incentives, and prescribed fire for ecosystem management. Issue 7 (1st September 2004) - Yoder, Jonathan; Engle, David; Fuhlendorf, Sam
Abstract : Prescribed fire is widely viewed as a useful but risky ecosystem management tool, and liability is a crucial issue for prescribed burning on private and public land. Basic liability rules motivate landowners to reduce risk when making choices about the use of fire. Liability therefore influences land use through incentives, and so has important consequences for the larger ecological landscape. Strict liability rules may lead to too little prescribed fire use, while negligence rules may, under certain circumstances, lead to too much. Although prescribed fire provides broad public benefits, such as reduction of wildfire risk or enhanced ecosystem health, the application of liability rules by courts often discourages its use as a vegetation management option. Various approaches exist for improving the laws and regulations surrounding prescribed fire.